EVALUACIÓN DE UNA TÉCNICA BILAMINAR PARA CUBRIR RECESIONES GINGIVALES (2018)
Objective: The purpose of this study was to evaluate, over a two year period, the decrease of gingival recession by using a Bilaminar Technique with a subepithellial free connective tissue graft placed under a coronally advanced full-thickness pedicle flap.Material and methods: Twenty buccal recessions (mean 3.4 mm; range 3 to 4 mm; Miller Class I, II) in 10 patients were treated, using a bilaminar technique by a combination of a subepithelial connective tissue graft placed under a coronally advanced full-thickness pedicle flap. Amount of gingival recession (GR), clinical attachments loss (CAL), and width of keratinized gingiva (WKG) were followed for 2 years after surgery. The measurements were performed at presurgery, and 1, 3, 6, 12, 18 and 24 months postsurgery. The descriptive statistic was expressed with averages plus standard deviation (SD). The longitudinal variations were evaluated by means of variance analysis (RG, creeping attachment, NIC and AEQ) or test of Friedman (IP and IG).Results: GR decreased from 3.4 ± 0.58 mm at baseline to 0.31 ± 0.43 at 24 months, which means a decrease of 3.16 mm, corresponding to 91.2% mean root coverage. CAL was significantly decreased at 24 months from 5.06 ± 0.71 to 2.10 ± 0.58. At 24 months, 3.17 of attachment gain was obtained. WKG significantly increased after 24 months (1.98). GR, CAL, and WKG had the most positive outcomes at 12 months and were maintained at stable levels throughout the 24 month observation period.Conclusions: The bilaminar technique employing a connective tissue graft with a partial thickness coronal advancement pedicle is a predictable method for root coverage and the clinical outcomes gained by this technique can be well maintained.